Association between pregnancy intention and optimal breastfeeding practices in the Philippines - Ulep, Valerie Gilbert T.
Background: The effect of pregnancy intention on post-natal practices like breastfeeding is still poorly understood in the Philippines. In this light, this study aims to determine the association between pregnancy intention and breastfeeding initiation and duration in the country. Methodology: This is a cross-sectional study design using the 2003 Philippine National Demographic and Health Survey. Logistic regression analysis was used to determine the independent association of pregnancy intention and optimal breastfeeding practices. The study includes 3,044 last-born children aged 6-36 months at the time of survey. Dead children were also included as long as their age of death satisfies the age criterion. Results: Children borne from mistimed pregnancies are more likely to have late breastfeeding initiation compared to children borne from wanted pregnancies (OR=1.44; 90%Cl: 1.17-1.78). However, this occurs only among children belonging to households with low socio-economic status. Among children belonging to households with high socio-economic status, no significant effect of pregnancy intention on breast feeding initiation was observed. Children borne from unwanted pregnancies are less likely to have short breastfeeding duration (OR=0.60 90%Cl: 0.48-0.76). However, this occurs only among children belonging to households with high socio-economic status. No significant effect of pregnancy intention on breastfeeding duration was observed among children belonging to households with low socioeconomic status. Conclusion: In the Philippines, children borne from mistimed pregnancies are less likely to have breastfeeding initiation with the first hour. In contrast, children borne from unwanted pregnancies are more likely to have longer breastfeeding duration compared to children borne from wanted pregnancies. Policy interventions should be articulated to further strengthen reproductive health programs and evaluate marketing practices of formula milk companies